Assessment of the periapical health of abutment teeth: A retrospective radiological study - GÜMRÜ TARÇIN, BİRSAY; TARÇIN, BİLGE; TÜRKAYDIN, DİLEK; İRİBOZ, EMRE (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2015)
Aim: The aim was to examine the technical quality of root fillings and periapical status of root-filled and nonroot-filled teeth restored with crowns and bridge retainers through a retrospective analysis of orthopantomographs (OPTGs) in an adult Turkish subpopulation. Materials and Methods: In this study, the digital OPTGs of adult patients between the ages of 20 and 70 who appealed to the Endodontics Endodontics Department of the Dentistry Faculty at Marmara University (Istanbul, Turkey) for the first time to have their endodontic treatment needs met were used. The periapical health of all teeth restored with crowns and bridge retainers, and the technical quality of the root fillings on abutment teeth were evaluated by radiographic criteria. Results: The survey was carried out using the OPTGs of 1000 adult patients composed of 590 (59.0%) women and 410 (41.0%) men. 4656 (20.9%) of the totally examined 22280 teeth were with crowns and bridge retainers. 986 of the total abutment teeth were root-filled and 458 (46.5%) of them had apical periodontitis (AP) while 3670 of the total abutment teeth were nonroot-filled and 930 (25.3%) of them were with AP. The most commonly treated teeth were premolars (33.8%), followed by molars (26.2%), incisors (23.3%) and canines (16.7%). Technical quality was proved to be adequate in 27.5% of the root fillings. A higher frequency of AP was related to inadequate root fillings (P < 0.01). Conclusion: The frequency of root-filled abutment teeth with AP, nonroot-filled abutment teeth with AP, and technically inadequate root-fillings among teeth with crowns and bridge retainers was high in the selected adult population.
Keywords: Abutment teeth; apical periodontitis; endodontics; epidemiology; radiology; BEAM COMPUTED-TOMOGRAPHY; FIXED PARTIAL DENTURES; APICAL PERIODONTITIS; CROWNED TEETH; RADIOGRAPHY; PREVALENCE; ACCURACY